The Irish population of London, 1900-14 : connections and disconnections - Ní Dhulchaointigh, Giulia (Trinity College (Dublin, Ireland). Department of History, 2013)
This thesis examines Irish people in London from 1900 to 1914. The first part of this thesis examines Irish residential communities. Chapter 1 examines the Irish communities in Inner London by analysing Irish communities in three areas: Central London, the East End and Bermondsey, and Battersea. This chapter will show that the culture and economy of the local area in London where Irish communities existed had a strong influence on the life of Irish communities. Chapter 2 examines the factors that led to the formation of Irish communities in the suburbs of London. Suburban areas have not typically been thought of as important areas to examine in relation to Irish people’s lives in Britain.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin